2017
DOI: 10.1186/s13018-017-0615-y
|View full text |Cite
|
Sign up to set email alerts
|

Patella morphological alteration after patella instability in growing rabbits

Abstract: BackgroundThe shape of the patella has been considered to be a predisposing factor resulting in patellar instability, but the effects of abnormal patella position during its development are unclear. The present study evaluated patellar morphological changes after patella instability and evaluated the influence of patellar instability on the patella shape.MethodsTwenty rabbits that were 2 months old were included in the study. The left knee of each rabbit, defined as the experimental group (N = 20 knees/group),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
54
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(61 citation statements)
references
References 21 publications
7
54
0
Order By: Relevance
“…Just like the previous animal experiments [7,8,9,10,11], the outcomes of the studies indicates that the aberrant version of the femur may not only be the risk factor for patella dislocation, but also be the consequence of patella dislocation. After patella dislocation in growing rabbits, the morphology of patella, femoral trochlea and the version of the femur were found changed signi cantly.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Just like the previous animal experiments [7,8,9,10,11], the outcomes of the studies indicates that the aberrant version of the femur may not only be the risk factor for patella dislocation, but also be the consequence of patella dislocation. After patella dislocation in growing rabbits, the morphology of patella, femoral trochlea and the version of the femur were found changed signi cantly.…”
Section: Discussionsupporting
confidence: 52%
“…Previous animal studies have investigated the in uence of patella instability on the morphological development of the patellofemoral joint. Wang, Li and Niu observed femoral trochlear dysplasia and patellar dysplasia could occur after patella dislocation in growing rabbits [7,8,9]. Kaymaz reported after surgery for patella alta in growing rabbits, trochlea attening was found [10].…”
Section: Introductionmentioning
confidence: 94%
“…In the present study, the Wiberg-index and Wiberg-angle in the control group are almost same before surgery and at the last follow-up, which is consistent with the previous studies. On the other hand, the patella and femoral trochlea dysplasia can occur after patella dislocation [14,15,16]. This study and the study by Fu [18] showed signi cant morphological alteration of patella and femoral trochlea after surgical correction in the children with recurrent patella dislocation.…”
Section: Discussionsupporting
confidence: 49%
“…Combined with the previous study [14,15,16,18], the normal patella position with femoral trochlea is important for the patellofemoral development. Patellar and femoral trochlear dysplasia can occur after patella dislocation [14,15].…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation